Dry matter dynamics and carbon flux along riverine forests of Gori valley, Western Himalaya - Bisht, Soni; Bargali, Surendra Singh; Bargali, Kiran; Rawat, Yashwant Singh; Rawat, Gopal Singh (Frontiers in Forests and Global Change, 2023)
Riverine forests in the Himalaya represent biodiverse, dynamic and complex ecosystem that offers numerous ecosystem services to the local as well as downstream communities and also contribute to the regional carbon cycle. However, these forests have not been assessed for their contribution to dry matter dynamics and carbon flux. We studied these parameters along three classes of riverine forests in eastern Uttarakhand dominated by Macaranga, Alnus and Quercus-Machilus forest. Using volume equations, we assessed tree biomass, carbon storage and sequestration in the study area. The total standing tree biomass in Macaranga, Alnus and Quercus-Machilus forest ranged from 256.6–558.1 Mg ha-1, 460.7–485.8 Mg ha-1 and 508.6–692.1 Mg ha-1, respectively. A total of 77.6–79.6% of vegetation biomass was stored in the aboveground biomass and 20.4–22.4% in belowground plant parts across the riverine forests. The carbon stock in Macaranga forest ranged from 115.5–251.1 Mg ha-1, in Alnus (207.3–218.6 Mg ha-1) and in Quercus-Machilus forest from 228.9–311.4 Mg ha-1. The mean annual litterfall was accounted maximum for Quercus-Machilus forest (5.94±0.54 Mg ha-1yr-1) followed by Alnus (5.57±0.31 Mg ha-1yr-1) and Macaranga forest (4.67±0.39 Mg ha-1yr-1). The highest value of litterfall was recorded during summer (3.40±0.01 Mg ha-1yr-1) and lowest in winter season (0.74±0.01 Mg ha-1yr-1). The mean value of net primary productivity and carbon sequestration was estimated highest in Quercus-Machilus Forest (15.8±0.9 Mg ha-1yr-1 and 7.1±0.9 Mg C ha-1 yr-1, respectively) and minimum in Alnus forest (13.9±0.3 Mg ha-1yr-1 and 6.1±0.3 Mg C ha-1yr-1, respectively). The results highlight that riverine forests play critical role in providing a large sink for atmospheric CO2. To improve the sustainable ecosystem services and climate change mitigating, riverine forests must be managed and conserved effectively in the region.